The Dynamic Mathematics Software for Teaching Variance - Li Li; Haiming Tang (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2020)
Abstract. In traditional teaching, many teachers often ignore the process of students' knowledge exploration, devote themselves to instilling knowledge to students in a short time, and then adopt the sea of questions tactics. Such teaching is only limited to the stage of telling students what